Abstrak Strategi Media Loose Parts dalam Memacu Perkembangan Kognitif Anak di Kober Cempaka Putih - Hidayah, Nurtati; Rizal, Soni Samsu; Nurunnisa, Euis Cici (Addabani: Interdisciplinary Journal of Islamic Education, 2026)
Cognitive development is a fundamental aspect of early childhood education, laying the foundation for future mastery of thinking, reasoning, and problem-solving skills. However, observations indicate that children's numeracy skills in early childhood education institutions remain relatively low due to the dominance of conventional, passive learning. This study aims to improve children's cognitive development, particularly numeracy skills, through the application of loose parts play media such as bottle caps, small stones, used cardboard, and small pieces of wood. The research method used was the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted in two cycles in Kober Cempaka Putih, Pamarican District, Ciamis Regency, from August to September 2025, with 20 children (12 girls and 8 boys) as subjects. Data collection techniques included structured observation, documentation, and field notes, while data analysis used descriptive qualitative and quantitative methods, with percentages of developmental achievements. The results showed significant improvement in each cycle. In the pre-cycle, 35% of children were in the Beginning to Develop (MB) category, and only 20% achieved Very Good Development (BSB). After the first cycle, the MB category decreased to 25%, and the BSB category increased to 25%. In the second cycle, there were no more children in the MB category, with 75% of children achieving BSB and 25% in the Developing According to Expectations (BSH) category. These findings confirm that loose parts media effectively improve early childhood numeracy skills while fostering motivation, creativity, and enthusiasm in the learning process.